The quandary of a healthy (child) sibling stem cell donor - Manish Raturi (Indian Journal of Medical and Paediatric Oncology)
Feelings of abandonment in a healthy (child) sibling donor (HSD) merit ethical consideration; more so, when he is needed to undergo a minimally risky, yet painful, procedure of stem cell donation (SCD) for the benefit of his ill sibling (child suffering from blood cancer). The varied feelings of the HSD undergoing SCD procedure are being presented in the form of a poem.